MODERN TREATMENT OF POST-TRAUMATIC EXTRA-ARTICULAR DEFORMITY OF THE FEMUR - Romanenko, Kostiantyn; Doluda, Yaroslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The issue of adequate treatment of post-traumatic deformities of long bones has become more urgent due to the large number of injured as a result of combat trauma and the presence of residual displacement of fragments after primary care providing. Objective. On the basis of literature analysis and own clinical experience, present methods of treatment of post-traumatic extra-articular deformity of the distal part of the femur (DF). Methods. The available professional literature, publications in electronic systems Google Scholar, PubMed, ScienceDirect were analyzed. The results of treatment of 38 patients with post-traumatic extra-articular deformities of the DF, in which the fracture line was extended to the area of the joint at the time of the primary injury, were studied. To plan the surgical treatment, the author’s 3D-printing technology was used in 12 patients with the most complex cases. A clinical example is given. Results. Key moments of patient examination, principles of correction and approaches to its planning in case of DF multiplanar deformities are defined. The results of 3D-visualization and 3D-printing of the damaged segment during the examination and planning of deformity correction were evaluated. All patients to whom the 3D-modeling technique was applied were operated оn, considering the individual characteristics of the deformity. After each stage of surgical treatment, a course of individual rehabilitation treatment was carried out. Positive dynamics of functional results were obtained within 12 months according to SF-36 and AOFAS scales. Conclusions. The use of 3D-modeling during the planning of corrective surgery allows the surgeon to increase the accuracy of the correction and significantly reduce the time of the operation. Well-known and improved methods with individually selected rehabilitation, used for the treatment of post-traumatic extra-articular deformities of the distal femur contribute to faster recovery, avoiding potential complications and achieving positive functional outcome in such patients.